2012
DOI: 10.1104/pp.111.191700
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomic Analysis of Seed Maturation in Arabidopsis, Rapeseed, and Soybean      

Abstract: To characterize protein phosphorylation in developing seed, a large-scale, mass spectrometry-based phosphoproteomic study was performed on whole seeds at five sequential stages of development in soybean (Glycine max), rapeseed (Brassica napus), and Arabidopsis (Arabidopsis thaliana). Phosphopeptides were enriched from 0.5 mg of total peptides using a combined strategy of immobilized metal affinity and metal oxide affinity chromatography. Enriched phosphopeptides were analyzed by Orbitrap tandem mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
79
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 51 publications
8
79
0
Order By: Relevance
“…By genome annotation, protein kinases were found to make up about 5.5% of the Arabidopsis genome [4], which is nearly twice of that in human [5], indicating the high specificity and a complex network of phosphorylation events in plants [4]. In recent years, benefitting from the new advances in proteomics technologies including phosphopeptide enrichment, high-accuracy mass spectrometry (MS), and associated bioinformatics, large-scale analyses of protein phosphorylation have been carried out in variety of plant species including Medicago Truncatula [6], Oryza sativa [7], Glycine max [8], Brassica napus [8], and Arabidopsis thaliana [8][9][10][11][12][13][14][15][16][17][18]. However, our understanding of plant phosphoproteomes remains very limited with respect to their complexity and functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By genome annotation, protein kinases were found to make up about 5.5% of the Arabidopsis genome [4], which is nearly twice of that in human [5], indicating the high specificity and a complex network of phosphorylation events in plants [4]. In recent years, benefitting from the new advances in proteomics technologies including phosphopeptide enrichment, high-accuracy mass spectrometry (MS), and associated bioinformatics, large-scale analyses of protein phosphorylation have been carried out in variety of plant species including Medicago Truncatula [6], Oryza sativa [7], Glycine max [8], Brassica napus [8], and Arabidopsis thaliana [8][9][10][11][12][13][14][15][16][17][18]. However, our understanding of plant phosphoproteomes remains very limited with respect to their complexity and functions.…”
Section: Introductionmentioning
confidence: 99%
“…First, the Ti 4+ -IMAC was used for phosphopeptide enrichment, and then the online MudPIT equipped with a RP-SCX biphasic column was employed for phosphopeptide fractionation. Through two duplicated MS runs, a total of 5348 unique phosphopeptides were identified, which represent 2552 unique phosphoproteins and are among the largest phosphorylation data sets reported in plants by far [7][8][9][10][11][12][13][14][15][16][17]. Further phosphorylation motif and pathway analysis revealed known and novel kinase recognition motifs and provided new insights into the phosphorylation network regulating both metabolic and signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, reverse phosphorylation of the phytohormone abscisic acid (ABA) seems to play a crucial regulatory role in the synthesis of SSPs at the transcriptional level [11,12]. More specifically, phosphoproteome studies in rapeseed and rice reported that cruciferins and cupins achieve higher levels of phosphorylation at the late maturation stage [9,13]. In addition, mobilization of the major SSP in the common bean, phaseolin, was found to occur in germinating seeds through degradation of highly phosphorylated isoforms [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, the molecular mechanism that triggers the cleavage of the patatin along the tuber life cycle has not to date been identified. The regulatory mechanisms involved in the synthesis and degradation of storage proteins are better known in dry seeds [8][9][10][11][12][13]. Phosphorylation has proven to be a key regulator mechanism in the maturation, dormancy and germination of seed storage proteins (SSPs).…”
Section: Introductionmentioning
confidence: 99%
“…Other properties of the plant hetACCase suggest additional, noncatalytic components may be involved in its function or regulation: (1) the observed size of the plant hetACCase complex is larger than the calculated mass of the known subunits (Reverdatto et al, 1999;Olinares et al, 2010); (2) the a-and b-CT subunits contain large domains of 200 to 300 residues that are not required for catalytic activity, are not present in prokaryotic homologs, and have no known function (Kozaki et al, 2001;Cronan and Waldrop, 2002); (3) the CT subcomplex associates with the plastid inner envelope through an unknown, non-ionic interaction (Thelen and Ohlrogge, 2002b); and 4) the a-CT subunit is phosphorylated on multiple sites but its functional role is unclear (Nakagami et al, 2010;Meyer et al, 2012). Collectively, these observations suggest that hetACCase may possess additional factors that facilitate the various forms of regulation.…”
Section: Introductionmentioning
confidence: 99%